2021
DOI: 10.1186/s13052-021-00981-1
|View full text |Cite
|
Sign up to set email alerts
|

Hookworm infection in infants: a case report and review of literature

Abstract: Background Hookworm infections (Necator americanus, Ancylostoma duodenale) are common in rural areas of tropical and subtropical countries. Human acquisition results from direct percutaneous invasion of infective larvae from contaminated soil. Overall, almost 472 million people in developing rural countries are infected. According to simulation models, hookworm disease has a global financial impact of over US$100 billion a year. Hookworm infection in newborn or infancy is rare, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
(32 reference statements)
1
10
0
1
Order By: Relevance
“…Children's hookworm infection was strongly correlated with the family income of the head of the household. The results are consistent with a study conducted in Côte d'Ivoire among school-age children, which revealed that the occupation of the parents was substantially related to the child's hookworm infection [25]. The low financial standing of family heads is most likely to blame for the tendency in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Children's hookworm infection was strongly correlated with the family income of the head of the household. The results are consistent with a study conducted in Côte d'Ivoire among school-age children, which revealed that the occupation of the parents was substantially related to the child's hookworm infection [25]. The low financial standing of family heads is most likely to blame for the tendency in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…According to the CDC (US centers for disease control and prevention) up to 1.12 billion, 795 million, and 740 million people suffer from Ascaris, whipworm, and hookworms, respectively [ 7 ]. Helminth infections may lead to cognitive impairment [ 8 ], tissue damage [ 9 ], pregnancy complications [ 10 ], and numerous other symptoms and can sometimes be fatal [ 11 ]. The high prevalence, detrimental effects, and increasing drug resistance of helminths [ 12 , 13 ] have led to much research on developing vaccines [ 14 , 15 , 16 , 17 , 18 ]; however, despite promising results, there is still much to be done to achieve final success.…”
Section: Helminthsmentioning
confidence: 99%
“…Additionally, its eggs can remain dormant and tolerate adverse conditions in the soil for up to 10 years [ 91 ]. Hookworm infection is usually associated with bare skin contact with contaminated soil containing third-stage larvae [ 9 ]. S. mansoni infection is a consequence of contact with environmental freshwater infested with parasite larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The main modes of contamination by these parasites are the eggs present in the stools of infected people or the larvae. Adult worms, which are located in the gut of an infected person, can produce thousands of eggs every day, contaminating environments that lack adequate sanitation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%